A method for preparing antibacterial porcelain glaze

Through the synergistic effect of modified titanium dioxide and nanobis tungstate, combined with plasma treatment and loaded yttrium and europium ion technology, the problem of poor glaze strength and dispersion of existing antibacterial porcelain products is solved, and the glaze is efficient and antibacterial and high Strength effect.

CN118619550BActive Publication Date: 2024-12-27CHAOZHOU CHAOAN DISTRICT YALAIER CERAMICS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410896138.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-05
Publication Date
2024-12-27
Estimated Expiration
2044-07-05

AI Technical Summary

Technical Problem

When the existing antibacterial porcelain glaze reacts with the porcelain blank at high temperature, the mechanical strength is low, resulting in poor dispersion of the glaze layer, which cannot effectively improve the antibacterial properties of the porcelain products and the strength of the glaze layer.

Method used

Potassium feldspar, sodium feldspar, kaolin, cordierite and hydroxyapatite are used as mixture A, and their dispersion is improved by plasma treatment; sodium hexametaphosphate, alumina, zirconia, antibacterial agent and dispersant are used As the mixture B, the antibacterial agent is mixed with modified titanium dioxide and nano-bismuth tungstate to achieve antibacterial effects through the generation of photogenerated electrons and reactive oxygen species, and the density and antibacterial properties of the glaze layer are improved by loading yttrium ions and europium ions.

Benefits of technology

The stable dispersion and high strength of the glaze are achieved, the antibacterial properties of porcelain products and the mechanical strength of the glaze layer are significantly improved, and the application prospects of glaze materials for antibacterial porcelain products are expanded.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of glazes, and specifically discloses a method for preparing an antibacterial porcelain product glaze, comprising the following steps: S1, crushing, grinding, and plasma treating potassium feldspar, sodium feldspar, kaolin, cordierite, and hydroxyapatite to obtain a mixture A; S2, adding sodium hexametaphosphate, aluminum oxide, zirconium oxide, an antibacterial agent, and a dispersant into water, and grinding to obtain a mixture B; S3, uniformly mixing the mixture A and the mixture B to obtain an antibacterial porcelain product glaze; the antibacterial agent is obtained by mixing modified titanium dioxide and nano-bismuth tungstate; the above method has simple steps and low cost, and the obtained glaze has good dispersion stability, and forms an antibacterial and hard glaze layer on the surface of the porcelain product, with excellent comprehensive performance and a wide range of applications.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of glazes, and more specifically, to a method for preparing an antibacterial porcelain product glaze. Background Art

[0002] With the rapid development of society, people's living standards are constantly improving, and people's health awareness is also increasing. In daily life, a large number of bacteria will adhere to the surface of porcelain products, causing certain harm to people's bodies and threatening their health; therefore, people's demand for antibacterial porcelain products has increased, and antibacterial porcelain products should be used in various occasions to effectively prevent the spread of bacteria and diseases.

[0003] Antibacterial porcelain products are mainly made of antibacterial glaze that chemically reacts and melts with the porcelain body at high temperature, forming an antibacterial coating on the surface of the porcelain. This not only prevents the spread of bacteria and diseases, but also increases the beauty of the porcelain, making it easier to wash and preventing it from being stained by dust.

[0004] At present, CN111559869A discloses an antibacterial glaze, an antibacterial glazed tile and a preparation method thereof, wherein the antibacterial glaze comprises the following components by weight: 5-10 parts of an encapsulated antibacterial agent and 90-100 parts of a transparent glaze; the encapsulated antibacterial agent comprises an envelope and a nano antibacterial agent wrapped by the envelope, wherein the envelope is aluminum oxide or silicon oxide, and the antibacterial agent is nano zinc oxide, nano silver oxide or nano titanium oxide; although the antibacterial durability is effectively improved, the mechanical strength of the glaze layer of the antibacterial porcelain product is relatively low due to the poor dispersion between the components; therefore, it is urgent to propose a preparation method for an antibacterial porcelain product glaze, which can not only improve the antibacterial performance of the porcelain product, but also enhance the strength of the glaze layer, thereby expanding the market prospects of the antibacterial porcelain product glaze. Summary of the invention

[0005] In order to improve the problems of poor antibacterial performance and glaze layer strength of existing porcelain products, the present application provides a method for preparing an antibacterial porcelain product glaze.

[0006] The present application provides a method for preparing an antibacterial porcelain glaze, which adopts the following technical solution:

[0007] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0008] S1, crushing, grinding, and plasma treating potassium feldspar, sodium feldspar, kaolin, cordierite, and hydroxyapatite to obtain a mixture A;

[0009] S2, adding sodium hexametaphosphate, aluminum oxide, zirconium oxide, an antibacterial agent, and a dispersant into water, and grinding to obtain a mixture B;

[0010] S3, after the mixed material A and the mixed material B are evenly mixed, the antibacterial porcelain product glaze is obtained;

[0011] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate.

[0012] By adopting the above technical scheme, the present application uses potassium feldspar, sodium feldspar, kaolin, cordierite and hydroxyapatite as raw materials of mixture A, and performs crushing, grinding and plasma treatment to increase the number of surface active sites of mixture A, improve the dispersibility of mixture A, and strengthen the adhesion between mixture A and mixture B; sodium hexametaphosphate, aluminum oxide, zirconium oxide, antibacterial agent and dispersant are used as raw materials of mixture B, and the antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate. Under the action of visible light or ultraviolet light, the two can achieve dual absorption of ultraviolet light and visible light, transfer electrons and holes to each other, enhance the generation of photogenerated electrons and reactive oxygen, destroy bacterial cell membranes and metabolic processes, and achieve significant antibacterial effects.

[0013] The preparation method of the present application is simple to operate and has low preparation cost. The obtained glaze has good dispersion stability and can form an antibacterial and hard glaze layer on the surface of porcelain products. It has excellent comprehensive performance and a wide range of applications.

[0014] Preferably, the modified titanium dioxide is prepared by the following method:

[0015] First, add succinic acid and template into isopropanol, mix evenly at 30-40°C, then add isopropyl titanate, stir and react at 60-70°C for 1-2h, finally slowly add a mixed solution of yttrium chloride and europium chloride, age for 2-3h, crystallize at 125-135°C for 20-30h, cool, filter and vacuum dry to obtain modified titanium dioxide.

[0016] Preferably, the mass ratio of the mixed solution of succinic acid, template, isopropanol, isopropyl titanate, yttrium chloride and europium chloride is 1-6:5-8:20-40:80:7-10.

[0017] Preferably, the template is obtained by mixing 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipid in a mass ratio of 2-8:7.

[0018] Preferably, the mixed solution of yttrium chloride and europium chloride is obtained by mixing yttrium chloride, europium chloride and water in a mass ratio of 3:2-5:40.

[0019] By adopting the above technical scheme, the present application uses succinic acid, template, isopropanol, isopropyl titanate, a mixed solution of yttrium chloride and europium chloride as raw materials to prepare modified titanium dioxide, and controls various process parameters so that the obtained modified titanium dioxide successfully loads yttrium ions and europium ions. The three elements of titanium, yttrium and europium work together to produce hydroxyl groups on the surface of the modified titanium dioxide for capturing free holes, forming hydroxyl radicals, and free free electrons combine with absorbed oxygen to form superoxide radicals; hydroxyl radicals, superoxide radicals and yttrium and europium elements jointly destroy the cells of microorganisms, inhibit the growth of microorganisms, and achieve an antibacterial effect.

[0020] In addition, the template of the present application is a mixture of 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipids, which can form porous nano-titanium dioxide. The yttrium ions and europium ions will be loaded inside and outside the pores. During the sintering process, they are not easily dissolved, thereby improving the durability of the sterilization. At the same time, the yttrium ions and europium ions loaded on the outside of the pores can increase the density of the glaze layer, thereby enhancing the strength of the glaze layer. Therefore, the modified titanium dioxide of the present application can effectively improve the antibacterial effect and the strength of the glaze layer.

[0021] Preferably, the mass ratio of the modified titanium dioxide to nano-bismuth tungstate is 4:2-7.

[0022] By adopting the above technical solution, the modified titanium dioxide and nano bismuth tungstate of the present application are mixed in a specific ratio, and the two work synergistically to better improve the antibacterial performance of the antibacterial agent.

[0023] Preferably, the mass ratio of potassium feldspar, sodium feldspar, kaolin, cordierite and hydroxyapatite in step S1 is 2-6:3-5:4-8:5:10.

[0024] Preferably, the mass ratio of sodium hexametaphosphate, aluminum oxide, zirconium oxide, antibacterial agent, dispersant and water in step S2 is 3-7:2-5:3:5-10:2-3:20.

[0025] Preferably, in step S3, the mass ratio of the mixture A to the mixture B is 7.1-13:9.

[0026] Preferably, the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5-7:8.

[0027] By adopting the above technical scheme, the dispersant of the present application is a mixture of polyethylene glycol and carboxymethyl cellulose, which effectively disperses the raw materials in the glaze, ensures good stability of the glaze, improves the density of the glaze layer, and thus increases the strength of the glaze layer.

[0028] Preferably, the alumina is γ-A1 2 O 3 .

[0029] Preferably, the zirconium oxide is m-ZrO 2 .

[0030] Preferably, the plasma conditions are: the gas source is oxygen, the processing frequency is 10-14 kHz, the processing power is 40-60 W, the processing time is 3-5 min, and the processing temperature is 40-60° C.

[0031] In summary, this application has the following beneficial effects:

[0032] The preparation method of the antibacterial porcelain product glaze of the present application has simple steps and low cost. Potassium feldspar, sodium feldspar, kaolin, cordierite and hydroxyapatite are used as a mixture A, and the mixture A is plasma treated; sodium hexametaphosphate, aluminum oxide, zirconium oxide, an antibacterial agent and a dispersant are used as a mixture B, and the antibacterial agent is a mixture of modified titanium dioxide and nano-bismuth tungstate, and a large amount of yttrium ions and europium ions are loaded on the porous structure of the modified titanium dioxide; the mixture A and the mixture B interact with each other and promote each other, thereby improving the antibacterial performance of the glaze, strengthening the strength of the glaze layer, and expanding the application prospect of the glaze. DETAILED DESCRIPTION

[0033] The present application is further described in detail below with reference to the embodiments.

[0034] Preparation Examples 1-9 provide methods for preparing modified titanium dioxide.

[0035] Preparation Example 1

[0036] Modified titanium dioxide is prepared by the following method:

[0037] First, add 10g succinic acid and 50g template agent to 200g isopropanol, mix well at 30°C, then add 800g isopropyl titanate, stir and react at 60°C for 1h, finally slowly drop 70g mixed solution of yttrium chloride and europium chloride, age for 2h, crystallize at 125°C for 20h, cool to room temperature, filter, and vacuum dry at 50°C for 8h to obtain modified titanium dioxide;

[0038] The template agent is obtained by mixing 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipid in a mass ratio of 2:7; the mixed solution of yttrium chloride and europium chloride is obtained by mixing yttrium chloride, europium chloride and water in a mass ratio of 3:2:40.

[0039] Preparation Example 2

[0040] Modified titanium dioxide is prepared by the following method:

[0041] First, add 20g succinic acid and 55g template agent to 250g isopropanol, mix well at 32°C, then add 800g isopropyl titanate, stir and react at 63°C for 1.2h, finally slowly drop 75g mixed solution of yttrium chloride and europium chloride, age for 2.3h, crystallize at 128°C for 23h, cool to room temperature, filter, and vacuum dry at 55°C for 10h to obtain modified titanium dioxide;

[0042] The template agent is obtained by mixing 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipids in a mass ratio of 4:7; the mixed solution of yttrium chloride and europium chloride is obtained by mixing yttrium chloride, europium chloride and water in a mass ratio of 3:2.5:40.

[0043] Preparation Example 3

[0044] Modified titanium dioxide is prepared by the following method:

[0045] First, 30g of succinic acid and 60g of template agent were added to 300g of isopropanol, mixed at 35°C, and then 800g of isopropyl titanate was added. The mixture was stirred at 65°C for 1.5h, and finally 80g of a mixed solution of yttrium chloride and europium chloride was slowly added dropwise. After aging for 2.5h, the mixture was crystallized at 130°C for 25h, cooled to room temperature, filtered, and vacuum dried at 60°C for 12h to obtain modified titanium dioxide.

[0046] The template agent is obtained by mixing 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipid in a mass ratio of 5:7; the mixed solution of yttrium chloride and europium chloride is obtained by mixing yttrium chloride, europium chloride and water in a mass ratio of 3:3:40.

[0047] Preparation Example 4

[0048] Modified titanium dioxide is prepared by the following method:

[0049] First, add 50g of succinic acid and 70g of template agent to 350g of isopropanol at 38°C, mix well, then add 800g of isopropyl titanate, stir and react at 68°C for 1.8h, finally slowly drop 90g of a mixed solution of yttrium chloride and europium chloride, age for 2.8h, crystallize at 132°C for 28h, cool to room temperature, filter, and vacuum dry at 65°C for 15h to obtain modified titanium dioxide;

[0050] The template agent is obtained by mixing 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipid in a mass ratio of 6:7; the mixed solution of yttrium chloride and europium chloride is obtained by mixing yttrium chloride, europium chloride and water in a mass ratio of 3:4:40.

[0051] Preparation Example 5

[0052] Modified titanium dioxide is prepared by the following method:

[0053] First, add 60g of succinic acid and 80g of template agent to 400g of isopropanol, mix well at 40°C, then add 800g of isopropyl titanate, stir and react at 70°C for 2h, finally slowly drop 100g of a mixed solution of yttrium chloride and europium chloride, age for 3h, crystallize at 135°C for 30h, cool to room temperature, filter, and vacuum dry at 70°C for 16h to obtain modified titanium dioxide;

[0054] The template agent is obtained by mixing 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipids in a mass ratio of 8:7; the mixed solution of yttrium chloride and europium chloride is obtained by mixing yttrium chloride, europium chloride and water in a mass ratio of 3:5:40.

[0055] Preparation Example 6

[0056] Modified titanium dioxide is prepared by the following method:

[0057] First, add 10g succinic acid and 50g template agent to 200g isopropanol, mix well at 30°C, then add 800g isopropyl titanate, stir and react at 60°C for 1h, finally slowly drop 70g mixed solution of yttrium chloride and europium chloride, age for 2h, crystallize at 125°C for 20h, cool to room temperature, filter, and vacuum dry at 50°C for 8h to obtain modified titanium dioxide;

[0058] The template agent is sophorolipid; the mixed solution of yttrium chloride and europium chloride is obtained by mixing yttrium chloride, europium chloride and water in a mass ratio of 3:2:40.

[0059] Preparation Example 7

[0060] Modified titanium dioxide is prepared by the following method:

[0061] First, add 10g succinic acid and 50g template agent to 200g isopropanol, mix well at 30°C, then add 800g isopropyl titanate, stir and react at 60°C for 1h, finally slowly drop 70g mixed solution of yttrium chloride and europium chloride, age for 2h, crystallize at 125°C for 20h, cool to room temperature, filter, and vacuum dry at 50°C for 8h to obtain modified titanium dioxide;

[0062] The template agent is 1-butyl-3-methylimidazolium tetrafluoroborate; the mixed solution of yttrium chloride and europium chloride is obtained by mixing yttrium chloride, europium chloride and water in a mass ratio of 3:2:40.

[0063] Preparation Example 8

[0064] Modified titanium dioxide is prepared by the following method:

[0065] First, add 10g succinic acid and 50g template agent to 200g isopropanol, mix well at 30°C, then add 800g isopropyl titanate, stir and react at 60°C for 1h, finally slowly drop 70g yttrium chloride aqueous solution, age for 2h, crystallize at 125°C for 20h, cool to room temperature, filter, and vacuum dry at 50°C for 8h to obtain modified titanium dioxide;

[0066] The template agent is obtained by mixing 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipids in a mass ratio of 2:7; and the yttrium chloride aqueous solution is obtained by mixing yttrium chloride and water in a mass ratio of 5:40.

[0067] Preparation Example 9

[0068] Modified titanium dioxide is prepared by the following method:

[0069] First, 10g of succinic acid and 50g of template agent were added to 200g of isopropanol at 30°C, mixed evenly, and then 800g of isopropyl titanate was added. The mixture was stirred at 60°C for 1h, and finally 70g of europium chloride aqueous solution was slowly added dropwise. After aging for 2h, the mixture was crystallized at 125°C for 20h, cooled to room temperature, filtered, and vacuum dried at 50°C for 8h to obtain modified titanium dioxide.

[0070] The template agent is obtained by mixing 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipid in a mass ratio of 2:7; the europium chloride aqueous solution is obtained by mixing europium chloride and water in a mass ratio of 5:40.

[0071] Examples 1-15 provide a method for preparing an antibacterial porcelain product glaze.

[0072] Example 1

[0073] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0074] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0075] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0076] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0077] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:2, and the modified titanium dioxide is prepared by Preparation Example 1; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0078] Example 2

[0079] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0080] S1, 3 kg of potassium feldspar, 3.5 kg of sodium feldspar, 5 kg of kaolin, 5 kg of cordierite and 10 kg of hydroxyapatite were crushed, ground, and passed through a 120-mesh sieve, and then plasma treated for 3.5 min with oxygen as the gas source, a processing frequency of 11 kHz, a processing power of 45 W, and a processing temperature of 45° C. to obtain a mixture A;

[0081] S2, 4kg sodium hexametaphosphate, 3kg γ-A1 2 O 3 、3kg m-ZrO 2 , 6 kg of antibacterial agent and 2.3 kg of dispersant were added into 20 kg of water, ground, and passed through a 120-mesh sieve to obtain a mixture B;

[0082] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 8:9, and stirring at a speed of 700 r / min for 1.2 h to obtain an antibacterial porcelain product glaze;

[0083] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:3, and the modified titanium dioxide is prepared by Preparation Example 2; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5.5:8.

[0084] Example 3

[0085] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0086] S1, 4 kg of potassium feldspar, 4 kg of sodium feldspar, 6 kg of kaolin, 5 kg of cordierite and 10 kg of hydroxyapatite were crushed, ground, and passed through a 150-mesh sieve, and then plasma treated for 4 min with oxygen as the gas source, a processing frequency of 12 kHz, a processing power of 50 W, and a processing temperature of 50° C. to obtain a mixture A;

[0087] S2, 5kg sodium hexametaphosphate, 3.5kg γ-A1 2 O3 、3kg m-ZrO 2 , 7.5 kg of antibacterial agent and 2.5 kg of dispersant were added into 20 kg of water, ground, and passed through a 150-mesh sieve to obtain a mixture B;

[0088] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 8.5:9, and stirring at a speed of 800 r / min for 1.5 h to obtain an antibacterial porcelain product glaze;

[0089] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 1:1, and the modified titanium dioxide is prepared by Preparation Example 3; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 3:4.

[0090] Example 4

[0091] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0092] S1, 5 kg of potassium feldspar, 4.5 kg of sodium feldspar, 7 kg of kaolin, 5 kg of cordierite and 10 kg of hydroxyapatite were crushed, ground, and passed through a 180-mesh sieve, and then plasma treated for 4.5 min with oxygen as the gas source, a processing frequency of 13 kHz, a processing power of 55 W, and a processing temperature of 55° C. to obtain a mixture A;

[0093] S2, 6.5kg sodium hexametaphosphate, 4.5kg γ-A1 2 O 3 、3kg m-ZrO 2 , 8 kg of antibacterial agent and 2.8 kg of dispersant were added into 20 kg of water, ground, and passed through a 180-mesh sieve to obtain a mixture B;

[0094] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 10:9, and stirring at a speed of 900 r / min for 1.8 h to obtain an antibacterial porcelain product glaze;

[0095] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 2:3, and the modified titanium dioxide is prepared by Preparation Example 4; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 3:4.

[0096] Example 5

[0097] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0098] S1, 6 kg of potassium feldspar, 5 kg of sodium feldspar, 8 kg of kaolin, 5 kg of cordierite and 10 kg of hydroxyapatite were crushed, ground, and passed through a 200-mesh sieve, and then plasma treated for 5 min with oxygen as the gas source, a processing frequency of 14 kHz, a processing power of 60 W, and a processing temperature of 60° C. to obtain a mixture A;

[0099] S2, 7kg sodium hexametaphosphate, 5kg γ-A1 2 O 3 、3kg m-ZrO 2 , 10 kg of antibacterial agent and 3 kg of dispersant were added into 20 kg of water, ground, and passed through a 200-mesh sieve to obtain a mixture B;

[0100] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 13:9, and stirring at a speed of 1000 r / min for 2 h to obtain an antibacterial porcelain product glaze;

[0101] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:7, and the modified titanium dioxide is prepared by Preparation Example 5; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 7:8.

[0102] Example 6

[0103] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0104] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0105] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0106] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0107] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:2, and the modified titanium dioxide is prepared by Preparation Example 6; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0108] Example 7

[0109] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0110] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0111] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0112] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0113] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:2, and the modified titanium dioxide is prepared by Preparation Example 7; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0114] Example 8

[0115] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0116] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0117] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0118] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0119] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:2, and the modified titanium dioxide is prepared by Preparation Example 8; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0120] Example 9

[0121] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0122] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0123] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0124] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0125] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:2, and the modified titanium dioxide is prepared by Preparation Example 9; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0126] Example 10

[0127] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0128] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0129] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0130] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0131] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 1:1, and the modified titanium dioxide is prepared by Preparation Example 1; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0132] Embodiment 11

[0133] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0134] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0135] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0136] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0137] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:7, and the modified titanium dioxide is prepared by Preparation Example 1; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0138] Example 12

[0139] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0140] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0141] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0142] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0143] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 10:1, and the modified titanium dioxide is prepared by Preparation Example 1; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0144] Embodiment 13

[0145] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0146] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0147] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0148] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0149] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 1:10, and the modified titanium dioxide is prepared by Preparation Example 1; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0150] Embodiment 14

[0151] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0152] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0153] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0154] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0155] The antibacterial agent is obtained by mixing modified titanium dioxide and nano-bismuth tungstate in a mass ratio of 4:2, and the modified titanium dioxide is prepared by Preparation Example 1; the dispersant is polyethylene glycol.

[0156] Embodiment 15

[0157] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0158] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0159] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0160] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0161] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:2, and the modified titanium dioxide is prepared by Preparation Example 1; the dispersant is carboxymethyl cellulose.

[0162] In order to verify the performance of the antibacterial porcelain glaze provided by the present application, the applicant set up comparative examples 1-5, wherein:

[0163] Comparative Example 1

[0164] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0165] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0166] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0167] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0168] The antibacterial agent is modified titanium dioxide, and the modified titanium dioxide is prepared by Preparation Example 1; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0169] Comparative Example 2

[0170] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0171] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0172] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0173] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0174] The antibacterial agent is nano bismuth tungstate; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0175] Comparative Example 3

[0176] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0177] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0178] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 2 kg of dispersant was added into 20 kg of water, and the mixture was ground and passed through a 100-mesh sieve to obtain a mixture B;

[0179] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0180] The dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0181] Comparative Example 4

[0182] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0183] S1, 2kg of potassium feldspar, 3kg of sodium feldspar, 4kg of kaolin, 5kg of cordierite and 10kg of hydroxyapatite were crushed, ground, and passed through a 100-mesh sieve, and then plasma treated for 3 minutes with oxygen as the gas source, a processing frequency of 10kHz, a processing power of 40W, and a processing temperature of 40°C to obtain a mixture A;

[0184] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 5 kg of antibacterial agent was added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain mixed material B;

[0185] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0186] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:2, and the modified titanium dioxide is prepared by Preparation Example 1.

[0187] Comparative Example 5

[0188] A method for preparing an antibacterial porcelain glaze comprises the following steps:

[0189] S1, crushing and grinding 2 kg of potassium feldspar, 3 kg of sodium feldspar, 4 kg of kaolin, 5 kg of cordierite and 10 kg of hydroxyapatite, and passing through a 100-mesh sieve to obtain a mixture A;

[0190] S2, 3kg sodium hexametaphosphate, 2kg γ-A1 2 O 3 、3kg m-ZrO 2 , 5 kg of antibacterial agent and 2 kg of dispersant were added into 20 kg of water, ground, and passed through a 100-mesh sieve to obtain a mixture B;

[0191] S3, mixing the mixed material A obtained in step S1 and the mixed material B obtained in step S2 at a mass ratio of 7.1:9, and stirring at a speed of 600 r / min for 1 h to obtain an antibacterial porcelain product glaze;

[0192] The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate in a mass ratio of 4:2, and the modified titanium dioxide is prepared by Preparation Example 1; the dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5:8.

[0193] The glazes obtained in Examples 1-15 of the present application and Comparative Examples 1-5 were respectively mixed with water to prepare 80wt% glaze slurry, coated on the surface of the porcelain product body, and fired at 1200°C to obtain a porcelain product; the antibacterial performance was tested according to Appendix A of JC / T897-2014 (2017), and the experimental bacteria were Escherichia coli and Staphylococcus aureus; the compressive strength was tested according to GB / T4740-1999, and the following result parameters were obtained, as shown in Table 1.

[0194] Table 1:

[0195]

[0196] It can be seen from the data shown in Table 1 above that the comprehensive performance of the glazes obtained in Examples 1-15 of the present application is far better than the glazes obtained in Comparative Examples 1-5. The glazes obtained in Examples 1-15 not only have excellent antibacterial properties, but also the strength of the glaze layer is greatly improved.

[0197] It can be seen from Examples 1, 6 and 7 that the modified titanium dioxide of Example 1 is prepared by Preparation Example 1, and the template used is a mixture of 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipids. Compared with Examples 6 and 7, the antibacterial properties of the glaze obtained in Example 1 and the strength of the glaze layer are significantly improved.

[0198] It can be seen from Examples 1, 8 and 9 that the modified titanium dioxide of Example 1 is prepared by Preparation Example 1, and during the preparation process, a mixed solution of yttrium chloride and europium chloride is added dropwise. Compared with Comparative Examples 8 and 9, the antibacterial property of the coating obtained in Example 1 is significantly improved.

[0199] It can be seen from Example 1 and Comparative Examples 1-3 that an antibacterial agent is added to Example 1, and the antibacterial agent is a mixture of modified titanium dioxide and nano-bismuth tungstate. Compared with Comparative Examples 1-3, the antibacterial property of the glaze obtained in Example 1 is improved, and the strength of the glaze layer is also enhanced; further comparison of Examples 1 and 10-13 shows that the mass ratio of modified titanium dioxide and nano-bismuth tungstate in Examples 1, 10, and 11 is in the range of 4:2-7, and the comprehensive performance of the glaze obtained in Example 1 is better than that in Examples 12 and 13.

[0200] It can be seen from Examples 1, 14, 15 and Comparative Example 4 that in Example 1, a dispersant is added, and the dispersant is a mixture of polyethylene glycol and carboxymethyl cellulose. Compared with Examples 14, 15 and Comparative Example 4, the compressive strength of the glaze layer obtained in Example 1 is significantly enhanced when the glaze is applied on the surface of the porcelain product.

[0201] It can be seen from Example 1 and Comparative Example 5 that after the mixed material A of Example 1 is subjected to plasma treatment, the comprehensive performance of the glaze obtained in Example 1 is better than that in Comparative Example 5.

[0202] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing an antibacterial porcelain glaze, characterized in that: The following steps are involved: S1, crushing, grinding, and plasma treating potassium feldspar, sodium feldspar, kaolin, cordierite, and hydroxyapatite to obtain a mixture A; S2, adding sodium hexametaphosphate, aluminum oxide, zirconium oxide, an antibacterial agent, and a dispersant into water, and grinding to obtain a mixture B; S3, after the mixed material A and the mixed material B are evenly mixed, the antibacterial porcelain product glaze is obtained; The antibacterial agent is obtained by mixing modified titanium dioxide and nano bismuth tungstate; The modified titanium dioxide is prepared by the following method: first, succinic acid and a template are added to isopropanol, mixed at 30-40° C., isopropyl titanate is added, stirred at 60-70° C. for reaction for 1-2 hours, and finally a mixed solution of yttrium chloride and europium chloride is slowly added dropwise, aged for 2-3 hours, crystallized at 125-135° C. for 20-30 hours, cooled, filtered, and vacuum dried to obtain the modified titanium dioxide; The mass ratio of the mixed solution of succinic acid, template, isopropanol, isopropyl titanate, yttrium chloride and europium chloride is 1-6:5-8:20-40:80:7-10; The template is obtained by mixing 1-butyl-3-methylimidazolium tetrafluoroborate and sophorolipid in a mass ratio of 2-8:7; The mixed solution of yttrium chloride and europium chloride is obtained by mixing yttrium chloride, europium chloride and water in a mass ratio of 3:2-5:40; The mass ratio of the modified titanium dioxide to the nano-bismuth tungstate is 4:2-7.

2. The method for preparing the antibacterial porcelain glaze according to claim 1, characterized in that: The mass ratio of potassium feldspar, sodium feldspar, kaolin, cordierite and hydroxyapatite in step S1 is 2-6:3-5:4-8:5:

10.

3. The method for preparing the antibacterial porcelain glaze according to claim 1, characterized in that: The mass ratio of sodium hexametaphosphate, aluminum oxide, zirconium oxide, antibacterial agent, dispersant and water in step S2 is 3-7:2-5:3:5-10:2-3:

20.

4. The method for preparing the antibacterial porcelain glaze according to claim 1, characterized in that: The mass ratio of the mixture A to the mixture B in step S3 is 7.1-13:

9.

5. The method for preparing the antibacterial porcelain glaze according to claim 1, characterized in that: The dispersant is obtained by mixing polyethylene glycol and carboxymethyl cellulose in a mass ratio of 5-7:8.

Citation Information

Patent Citations

  • Bismuth tungstate composite photocatalyst, preparation method thereof, and application thereof

    CN102335602A

  • Antibacterial glaze composition and ceramic product prepared from same

    CN109052952A